A new and efficient synthesis of 1,3,4-oxadiazole derivatives using TBTU - Maghari, Shokoofeh; Ramezanpour, Sorour; Darvish, Fatemeh; Balalaie, Saeed; Rominger, Frank; Bijanzadeh, Hamid Reza (Tetrahedron, 2013)
An efficient method for the synthesis of 2,5-disubstituted 1,3,4-oxadiazoles from isothiocyanates and hydrazides through cyclodesulfurization in the presence of (O-(benzotriazol-1-yl)-N,N,N′,N′-tetramethyluronium tetrafluoroborate) TBTU as an uronium coupling reagent has been developed. The present methodology offers several advantages, such as simple and easy work-up procedures, mild reaction conditions and it is environmentally benign.